Pathogenicity of missense variants affecting the collagen IV α5 carboxy non-collagenous domain in X-linked Alport syndrome - Joel T. Gibson; Omid Sadeghi-Alavijeh; Daniel P. Gale; Hansjörg Rothe; Genomics England Research Consortium; Judy Savige (Scientific Reports, 2022)
Abstract X-linked Alport syndrome is a genetic kidney disease caused by pathogenic COL4A5 variants, but little is known of the consequences of missense variants affecting the NC1 domain of the corresponding collagen IV α5 chain. This study examined these variants in a normal (gnomAD) and other databases (LOVD, Clin Var and 100,000 Genomes Project) to determine their pathogenicity and clinical significance. Males with Cys substitutions in the collagen IV α5 NC1 domain reported in LOVD (n = 25) were examined for typical Alport features, including age at kidney failure. All NC1 variants in LOVD (n = 86) were then assessed for structural damage using an online computational tool, Missense3D. Variants in the ClinVar, gnomAD and 100,000 Genomes Project databases were also examined for structural effects. Predicted damage associated with NC1 substitutions was then correlated with the level of conservation of the affected residues. Cys substitutions in males were associated with the typical features of X-linked Alport syndrome, with a median age at kidney failure of 31 years. NC1 substitutions predicted to cause structural damage were overrepresented in LOVD (p < 0.001), and those affecting Cys residues or ‘buried’ Gly residues were more common than expected (both p < 0.001). Most NC1 substitutions in gnomAD (88%) were predicted to be structurally-neutral. Substitutions affecting conserved residues resulted in more structural damage than those affecting non-conserved residues (p < 0.001). Many pathogenic missense variants affecting the collagen IV α5 NC1 domain have their effect through molecular structural damage and 3D modelling is a useful tool in their assessment.